Juridical Analysis Of Child Grooming And Identify Forgery (Faker) In The Roleplayer Community On Social Media - Jamaila, Jasmine Fatiha; Wahyuningsih, Yuliana Yuli (Journal of Law, Politic and Humanities, 2025)
This study examines the modus operandi of child grooming that utilizes identity forgery (faker) in the online roleplayer (RP) community, as well as analyzes legal protection and psychological impact on victims. Using a normative juridical approach, the study found that perpetrators systematically build an emotional relationship with child victims through false identities for the purpose of exploitation. This faker practice has been shown to cause deep psychological trauma and mental destruction. Juridically, this action can be charged through Article 378 of the Criminal Code concerning fraud, the Child Protection Law, and the ITE Law. The results of the study confirm the importance of digital literacy, parental supervision, and ongoing psychological support for victims. We suggest the need for more protective platform policies and legal adaptations that are responsive to these cybercrimes. Keywords: Child grooming, identity forgery, roleplayer, child protection, cyber law.